Structural studies of the polymorphs of carbamazepine, its dihydrate, and two solvates - Harris, R; Ghi, P; Puschmann, H; Apperley, D; Griesser, U; Hammond, R; Ma, C; Roberts, K; Pearce, G; Yates, JR; Pickard, C (2005)
High-field cross-polarisation magic-angle spinning 13C NMR spectra are presented for the four known polymorphe of anhydrous carbamazepine, for a dihydrate, and for two solvates. These are all distinctive, despite relatively low spectral dispersion, and give immediate information about the cristallographic asymmetric unit. The results for the trigonal and the two monoclinic forms are consistent with the published crystal structures. That of the triclinic form was found to contain four molecules in the crystallographic asymmetric unit, which has recently been confirmed by an X-ray diffraction study. NMR shows that the dihydrate has one molecule in the asymmetric unit, and the full crystal structure derived from single-crystal X-ray diffraction work is reported herein. It is found to be ordered and monoclinic, in contrast to the reported disordered orthorhombic structure. The discrepancy is attributed to the common occurrence of multiple micro-twinning. Shielding computations using a method which takes explicit account of the repetition inherent in a crystal lattice are reported for the P-monoclinic form and are compared to the experimental chemical shifts. The NMR data of all the forms are discussed in relation to variations in the molecular geometry of the hydrogen-bonded dimers (except in the case of two solvates). Chemical shift variations are explored as a function of the amide torsion using the Gaussian computer program. © 2005 American Chemical Society.